Oral/Aural: Pastness and Sound as Medium and Method - Erasmus, Aidan; Layne, Valmont (Kronos (Bellville, South Africa), 2023)
In archival footage uploaded online of a concert at the University of the Western Cape in 1988 musician Robbie Jansen declared that the next composition to be performed was named 'Freedom Where Have You Been'.1 Before counting the band in, Jansen offered a short discourse on the meaning of the phrase hoya chibongo. Hearing the Afrikaans hoorie (meaning listen here) in the expression hoya, Jansen proceeded to split up the word chibongo to accentuate chi- as aurally reminiscent of the suffix -tjie that is used in Afrikaans to mark the diminutive. bongo, in this context as Jansen remarked, is the drum, leading Jansen to exclaim that the phrase hoya chibongo means to 'listen to the (small) drum', the drum that is, according to Jansen, 'the truth'. In Jansen's exact words, 'the drum speaks the truth and the drum has always been our language before these funny words that we are speaking now'. Jansen's translation was markedly oral, not only in its expression of speech and languaging but also in its invocation of a historicity through the oral; an oral tradition, for all intents and purposes. In its locatedness in a musically expressive and performative moment, Jansen expressed a duality of sound that exceeds the oral itself: calling attention to how language might be a conduit for the instrument, and how in some sense the drum might speak across time and space. It usefully deepens the often cliché proclamation rehearsed in and out of music studies in particular that music is universal, or that sound might be thought of as a kind of connective tissue that allows a specific sense-making of the social.2 In Jansens invocation of 'before' in his statement about the drum as language, and in debates around the meaning of sound to the social, it is history - or, a representation of pastness - that is called upon to bring about a set of futures where sound mediates the experience of a temporal matrix where truth, or freedom, might be found. What Jansen does/did was not necessarily an act of translation into a local vernacular as it is the blurring of the oral and the aural in a moment that might express the relation between sound, its interpretation, and its social life, obliquely. The truth for Jansen was what the drum expressed; but it was also the drum itself. The oral is aural, as the aural is oral.